Primary School Children’s Progress in Indonesian Language: A Multilevel Analysis - Laurens Kaluge (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This study attempts to measure the child progress over a one-year period in Indonesian Language at the fourth grade of primary schools. The main problem was to what extent the school and pupil variances in language attainment were before and after taking into account the baseline, family background, classes, and school context. The multilevel analysis as a current promising analysis was used in modeling due to its better results in estimating the hierarchical characteristics of data. In addition to the school archives, the data were collected using questionnaires to 1668 children, 60 class-teachers, and 60 head-teachers. It was found that the significant predictors in estimating achievement progress were child gender and age, father’s educational background, teacher age, and the school meetings.